1998
DOI: 10.1176/ajp.155.4.555
|View full text |Cite
|
Sign up to set email alerts
|

Higher Prevalence of Obsessive-Compulsive Symptoms in Patients With Blepharospasm Than in Patients With Hemifacial Spasm

Abstract: The findings provide additional support for the hypothesis that obsessive-compulsive symptoms are related to basal ganglia dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
3
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 20 publications
5
39
3
8
Order By: Relevance
“…Our findings differ with previously reported increases of OCD/OCS in individuals with dystonia [Bihari et al, 1992a,b;Broocks et al, 1998;Wenzel et al, 1998Wenzel et al, , 2000Cavallaro et al, 2002;Moraru et al, 2002;Saunders-Pullman et al, 2002]. This inconsistency probably reflects differing subject groups; that is, previous studies focused on subjects with etiologies other than DYT1, including families with myoclonus dystonia linked to DYT11 and individuals with focal dystonia [Bihari et al, 1992a,b;Broocks et al, 1998;Wenzel et al, 1998Wenzel et al, , 2000Cavallaro et al, 2002;Moraru et al, 2002]. The etiopathogenic and phenotypic differences between DYT1 dystonia and other dystonias, especially distinct involvement of fronto-striatal circuitry may explain the differences in OCD frequency among dystonia subtypes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings differ with previously reported increases of OCD/OCS in individuals with dystonia [Bihari et al, 1992a,b;Broocks et al, 1998;Wenzel et al, 1998Wenzel et al, , 2000Cavallaro et al, 2002;Moraru et al, 2002;Saunders-Pullman et al, 2002]. This inconsistency probably reflects differing subject groups; that is, previous studies focused on subjects with etiologies other than DYT1, including families with myoclonus dystonia linked to DYT11 and individuals with focal dystonia [Bihari et al, 1992a,b;Broocks et al, 1998;Wenzel et al, 1998Wenzel et al, , 2000Cavallaro et al, 2002;Moraru et al, 2002]. The etiopathogenic and phenotypic differences between DYT1 dystonia and other dystonias, especially distinct involvement of fronto-striatal circuitry may explain the differences in OCD frequency among dystonia subtypes.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies of primary dystonia have reported an increase of psychiatric symptoms, including depression and obsessive-compulsive disorder (OCD) or symptoms (OCS), in individuals with dystonia [Bihari et al, 1992a,b;Broocks et al, 1998;Wenzel et al, 1998;Wenzel et al, 2000;Cavallaro et al, 2002;Moraru et al, 2002;Saunders-Pullman et al, 2002]. Most of the previous studies involved patients with adult-onset of symptoms and were not restricted to a single genetic etiology.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, since both BS and HFS have similar profiles regarding response to treatment and subjective interference with social and occupational skills, both should also behave similarly in regards to psychopathological findings. Another hypothesis is that these patients indeed do not present relevant psychopathological abnormalities as demonstrated by Scheidt et al 36 on an investigation methodologically similar to the already cited Broocks et al 4 study that found opposing results. H o w e v e r, the former study evaluated a population significantly larger and with a broader and more complete assessment, less focused on obsessive and compulsive symptoms than the later.…”
Section: Discussionmentioning
confidence: 71%
“…This study used only a parametric scale that does not allow diagnosis and does not assess symptoms equally as in the case of the Yale-Brown scale, focusing more on compulsions as opposed to obsessive thinking. Broocks et al 4 used a methodology similar to our study comparing patients with BS and HFS, differing in regards to the size of the population (13 subjects in each group) and use of criteria and scales (DSM III R and Hamburg Obsessive-Compulsive Inventory). In their study, although the authors did not find cases that fulfilled the diagnostic criteria in either group, symptom scores were higher for the BS group in the comparison with the HFS group, reaching statistical significance (p=0.03).…”
Section: Discussionmentioning
confidence: 99%
“…Высокая частота тревожных заболеваний, включая обсес-сивно-компульсивные расстройства и социальную фобию у пациентов с фокальной дистонией, отмечена во многих исследованиях [12][13][14][15][16]. Так, в одном из исследований из 89 пациентов с фокальной дистонией 57,3% страдали различ-ными психиатрическими заболеваниями, которые сформи-ровались в среднем за 18,4 ± 13,9 года до начала дистонии [17].…”
Section: эмоциональные расстройстваunclassified